Optimal sizing and placement of multiple renewable distribution generation and DSTATCOM in radial distribution systems using hybrid lightning search algorithm‐simplex method optimization algorithm. (23rd September 2020) - Chinnaraj, Sakthi Gokul Rajan; Kuppan, Ravi
Abstract: In this literature, the simultaneous placement of both the Renewable Distribution Generation (DG) and Distribution STATCOM (DSTATCOM) in the Radial Distribution System (RDS) for Power Loss Minimization (PLM) is discussed. Loss Sensitivity Factor (LSF) is initially applied to discover the candidate location of DG and DSTATCOM in RDS. The effective Hybrid Lightning Search Algorithm‐Simplex Method (LSA‐SM) is used to compute the optimal sizing of DG and D‐STATCOM. The performance of the proposed method is tested separately on both IEEE33 and IEEE69 RDS test systems. The improvement in system Voltage Profile and operational stability before and after the allocation of DG and DSTATCOM is discussed. The improved system Voltage Stability Index values for different cases are plotted. The performance of the proposed method is compared with similar existing methods.